Development of a Prototype Room Security Monitoring System for Early Fire Detection Using a Prototyping Method Based on Sensors and IoT - Alfonsius, Eric (Department of Informatics Engineering, 2025)
Many public spaces have implemented monitoring systems to detect fires. Traditional fire monitoring systems typically involve manual supervision of each room, requiring personnel to physically visit locations daily, which is time-consuming and inefficient. This study aims to develop a prototype room security monitoring system designed for early fire detection. The system utilizes IoT technology and a web-based platform, allowing operators to monitor all rooms remotely. The prototype is equipped with fire detection sensors and an alarm system for real-time alerts. Each room is outfitted with a flame detector sensor operated by a microcontroller (Arduino Nano), which serves as the central control for all connected devices. To transmit data from the sensors to the web-based system, the prototype uses the ESP8266 Wi-Fi module, enabling seamless communication between the sensors and the monitoring platform. The system development was carried out using the prototyping method, which involved iterative design, construction, and testing. In addition, blackbox testing was conducted to evaluate the system's functionality without examining the internal code. The results indicate that the system successfully detects fires early and sends real-time notifications to the web platform with high accuracy. The system also allows for rapid operator response through the alarm system. Based on the blackbox testing results, all key features, such as fire detection, web notifications, and alarms, functioned as specified. Thus, this prototype is deemed effective in enhancing the efficiency of room security monitoring.